Characteristics of co-infections by HCV and HBV among Brazilian patients infected by HIV-1 and/or HTLV-1 - Moreira,Marcia (2013)
BACKGROUND: The human retroviruses HIV-1 and HTLV-1 share the routes of infection with hepatitis viruses B and C. Co-infection by these agents are a common event, but we have scarce knowledge on co-infection by two or more of these agents. OBJECTIVE: To evaluate the characteristics and risk factors for co-infections by HBV and HCV in patients infected by HIV-1 or/and HTLV-1, in Salvador, Brazil. METHODS: In a case-control study we evaluated patients followed in the AIDS and HTLV clinics of Federal University of Bahia Hospital. Clinical and epidemiological characteristics were reviewed, and patients were tested for the presence of serological markers of HBV and HCV infections. HCV-infected patients were tested by PCR to evaluate the presence of viremia. RESULTS: A total of 200 HIV-1, 213 HTLV-1-infected, and 38 HIV-HTLV-co-infected individuals were included. HIV-infected patients were more likely to have had more sexual partners in the lifetime than other patients' groups. HIV-HTLV-co-infected subjects were predominantly male. Patients infected by HTLV or co-infected had a significantly higher frequency of previous syphilis or gonorrhea, while HIV infection was mainly associated with HPV infection. Co-infection was significantly associated to intravenous drug use (IVDU). HBV and/or HCV markers were more frequently found among co-infected patients. HBV markers were more frequently detected among HIV-infected patients, while HCV was clearly associated with IVDU across all groups. AgHBs was strongly associated with co-infection by HIV-HTLV (OR = 22.03, 95% CI: 2.69-469.7), as well as confirmed HCV infection (p = 0.001). Concomitant HCV and HBV infection was also associated with retroviral co-infection. Patients infected by HTLV-1 had a lower chance of detectable HCV viremia (OR = 0.04, 95% CI: 0.002-0.85). CONCLUSIONS: Infection by HCV and/or HBV is frequent among patients presenting retroviral infection, but risk factors and prevalence for each infection are distinct for each agent. Retroviral co-infection increases the risk of a positive AgHBs, but HTLV-1 infection seems to increase the likelihood of HCV spontaneous clearance.